Transgenesis and Secondary Metabolism - Jha, Sumita; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This handbook provides comprehensive reference information on the efficient production of secondary metabolites from plants by transgenesis and other genetic manipulation strategies. It reviews and summarizes selected important case studies in genetic methods applied to enhance the production of a given metabolite or a group of related or derived compounds. Readers will find reference information on a multitude of techniques and methods, including traditional breeding and screening; over-expression of genes encoding key enzymes; functional genomics approaches; metabolic engineering of the relevant biosynthetic pathways; indirect genetic approaches to improve metabolite production, including Agrobacterium mediated transformations. Furthermore, combinatorial biochemistry approaches to engineer secondary metabolic pathways are summarized, which can offer access to new structures or to the design of novel compounds. Since many commercially valuablesubstances are still extracted from plants, being largely inaccessible to efficient modern laboratory synthesis methods, this book provides a valuable resource of information for biotechnological approaches that can help to find alternative and more efficient methods for the production of natural secondary metabolites. Thus adjusted production methods, with the help of tailored plant systems, can potentially help to release the stress on plants, which are currently suffering from extensive human harvesting, and to conserve global biodiversity. Readers will find comprehensive reference information on plant genetic manipulation toward more efficient synthesis, accumulation and production of target secondary metabolites. The handbook will appeal to researchers and professionals, but also graduate students and scholars working in the fields of biotechnology, genetic engineering, medicinal plant research, pharmacy, and phytochemistry.
Part I General Aspects of Transgenesis and Secondary Metabolism: DNA Transfer to Plants by Agrobacterium rhizogenes: A Model for Genetic Communication Between Species and Biospheres -- Secondary Metabolism and the Rationale for Systems Manipulation -- Plant Cell Cultures as Producers of Secondary Metabolites: Podophyllum Lignans as a Model -- Secondary Metabolite Production in Transformed Cultures -- Antimalarial Compound Synthesis from Transgenic Cultures -- Evaluation of Agrobacterium tumefaciens Usefulness for the Transformation of Sage (Salvia Officinalis L.) -- Ruta Graveolens: Phytochemistry, Pharmacology and Biotechnology -- Secondary Metabolite Profile of Transgenic Centaury (Centaurium erythraea Rafn.) Plants, Potential Producers of Anticancer Compounds -- Syzygium cumini (L.) Skeels: Cardiometabolic Properties and Potential Tissue Culture-Based Improvement of Secondary Metabolites Production -- Part II Hairy roots and Secondary Metabolism: Secondary Products from Plant Cell Cultures - Early Experiences with Agrobacterium rhizogenes-transformed Hairy Roots -- Secondary Metabolite Production in Transgenic Hairy Root Cultures of Cucurbits -- "Hairy Root" Technology: An Emerging Arena for Heterologous Expression of Biosynthetic Pathway Genes in Medicinal Plants -- Agrobacterium rhizogenes -Mediated Transformation in Medicinal Plants: Genetic Stability in Long Term Culture -- Biotransformation Through Hairy Roots: Perspectives, Outcomes, and Major Challenges -- Part III Metabolic Engineering: Metabolic Engineering of Lignan Biosynthesis Pathways for the Production of Transgenic Plant-Based Foods -- The Elucidation and Metabolic Engineering of Terpenoid Indole Alkaloid Pathway in Catharanthus roseus Hairy Roots -- Pathway Modulation of Medicinal and Aromatic Plants Through Metabolic Engineering Using Agrobacterium tumefaciens -- Metabolic Engineering for Improving the Production of Taxol -- Metabolic Engineering of Phenyl Propanoids in Plants -- Part IV Metabolic Phytochemistry and Functional Analysis: Metabolic Phytochemistry-Based Approaches for Studying Secondary Metabolism Using Transformed Root Culture Systems -- Functional Analysis and the Role of Members of SGT Gene Family of Withania somnifera -- Part V Applications and Future Prospects: Phytochemicals of Nematode-resistant Transgenic Plants -- Plant Molecular Pharming -- Biotechnological Approaches for Bioremediation: In Vitro Hairy Root Culture -- Genetic Manipulation and Its Contribution to Pharmaceuticals: Past and Future Perspectives.--.
Keywords: Biotechnology; Plant genetics; Botanical chemistry; Bioinformatics; Bioorganic chemistry; Pharmacy; Chemical Bioengineering; Plant Genetics; Plant Biochemistry; Computational and Systems Biology; Bioorganic Chemistry; Pharmacy